KONDISI GEOLOGI TEKNIK PASIR LEPAS TERHADAP PERENCANAAN DAN PRE-DESAIN BENDUNGAN TIPE URUGAN (EARTH DAM) DI DESA KANDANG AMPEK, KABUPATEN PARIAMAN, SUMATERA BARAT - -, Boy Yoseph (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
The Observatory area include in the fisiography of Rangkaian Pegunungan Barisan Barat, which is located at the elevation +604 m until +620 m above the sea level. Geologically is consist of two unit geomorphology, i.e geomorphology unit of breccia volcanic hilly extremely steep and geomorphology unit of breccia tuff hilly slope. These geomorphology condition in caused the hydraulic gradient quite high and so the speed of current surface water too. Litology of the observatory area is breccia volcanic. The geology structure of the observatory area which is holding a role is not found, but there are joints in several locations. Which were assumsed come from the tectonic activity which developed along the Sumatera Fault (Semangko Fault).Based on soil mecanic datas, the dam material has a relative session = 0 . Where as the (C) valve (cohessi) is very small, because of that the soil bearing capacity is very small, and its necessary to make a foundation. One of many years to increase Dr (relative session) from those material to mix soil (soil mixing) (to add the component cohesive /silt and clay). The Observatory area included to the earthquake area, so type of dam is earth dam. clay core on dam body is required to decrease the seepage. Dam body is consisted with the comparation of soil mix 9:1:0 and 8:1:1.